The Impact of Excessive Fructose Consumption on Kidney Health: A Narrative Review - Yani, Ahmad; Putri (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2023)
Fructose consumption has increased markedly in recent decades, paralleling the global rise in chronic kidney disease (CKD). This narrative review examines how excessive fructose intake impairs renal function through pathways involving oxidative stress, inflammation, uric acid metabolism, and insulin resistance. Peer reviewed studies from databases such as PubMed, Scopus, and Google Scholar were analyzed to explore the biological mechanisms linking fructose to renal dysfunction. The review reveals that high fructose diets especially those involving artificial sweeteners like high fructose corn syrup exacerbate kidney damage, promote hypertension, and accelerate fibrosis. Countries with high fructose intake show increased CKD prevalence, underscoring the urgency of public health responses. Although sugar reduction policies such as taxation and labeling regulations have shown promise, gaps remain in understanding long term metabolic effects and genetic interactions. Future research should focus on targeted interventions to mitigate fructose induced kidney injury. This study emphasizes the need for immediate, evidence based dietary and policy strategies to address the global burden of fructose related kidney disease.